PARAMETER BIOLOGI DAN PERTUMBUHAN IKAN SEMBILANG (Paraplotosus albilabris) TERTANGKAP DENGAN TRAP NET DI PERAIRAN KECAMATAN SEGERI KABUPATEN PANGKEP - Mustamin Tajuddin; Randi Randi; Beddu Tang; Muhammad Saenong (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2024)
The purpose of this study is to determine the distribution of size, length relationship, and weight of sembilang fish caught with trap nets in the waters of Segeri District, Pangkep Regency. The research was carried out in Segeri District, Pangkep Regency from June to December 2022. The research method uses the survey method, the data collected consists of primary data and secondary data. The results of this study are the distribution of the size of the caught sembilang fish in the average size range that reaches the beginning of adult growth, because the size of the caught fish is still below the maximum size growth. The relationship between the length and weight of the fish that is predominantly caught in the net trap is negative allometrics. With a negative allometric growth pattern, it means that the increase in length is faster than the increase in weight.